TiO2 as Second Phase in Na3Zr2Si2PO12 to Suppress Dendrite Growth in Sodium Metal Solid‐State Batteries. Issue 9 (24th January 2022) - Gao, Zhonghui; Yang, Jiayi; Li, Guanchen; Ferber, Thimo; Feng, Junrun; Li, Yuyu; Fu, Haoyu; Jaegermann, Wolfram; Monroe, Charles W.; Huang, Yunhui
Abstract: Solid‐state sodium–metal batteries will not achieve reasonable power density without electrolytes that solve the dendrite (filamentation) problem. Metal‐filament formation during plating at ceramic/metal interfaces can cause electrical failure by internal short‐circuit or mechanical failure by electrolyte fracture. Herein, an Na3 Zr2 Si2 PO12 (NZSP) sodium‐ion‐conducting NASICON electrolyte in which TiO2 is incorporated as an additive is presented, leading to a two‐phase composite NZSP(TiO2 ) with improved density, Young's modulus, hardness, grain structure, and bulk permittivity. These features of NZSP(TiO2 ) suppress dendrite growth along grain boundaries, microcracks, and micropores. As well as demonstrating ultralow ceramic/Na kinetic resistance with electrochemical measurements, X‐ray photoelectron spectroscopy is performed to probe interfacial reaction mechanisms. The TiO2 phase forms within grain boundaries and along NZSP surfaces. This modifies the two‐phase material's microstructure and improves its electrochemical performance, while also increasing the critical current density for dendrite formation. Design guidelines are discussed to mitigate microscopic defects and dendrites in two‐phase ceramic electrolytes. Abstract : TiO2 is incorporated into Na3 Zr2 Si2 PO12 as a second phase, which can improve density, make grains more adherent, reduce microscopic defects, and lower the interfacial resistance against metallic Na, thereby raising the critical current density.